Regional spillovers and economic growth: do neighbouring countries matter for Sabah and Sarawak economic development? - Habibullah, Muzafar Shah; Awang Marikan, Dayang Affizzah; Puah, Chin Hong; Abdul Hamid, Baharom (Penerbit Universiti Malaysia Terengganu, 2013)
The objective of the present paper is to address the question whether the economic development of the neighbouring countries, states or provinces have impacted the states of Sabah and Sarawak or vice versa. Using annual data for the period 1968 to 2003, results indicate that the growth of the state of Sarawak is affected by the growth of Brunei Darussalam, Sabah, West Kalimantan and East Kalimantan and the economy of Sabah is affected by the economies of Brunei, Sarawak and East Kalimantan.